Implementation of Martyrdom Values of Surah Al-Fatihah Verse 5 in Achieving Children's Educational Goals - Gusman Taufiq (Tarbiyah Departement collaboration with AMCA, 2022)
This study aims to determine the relationship between the ability to read the Qur'an and students' interest in learning with the learning outcomes of children's education. The problem in this study is implementing Children's Education at SD Negeri Mulyasari. II Dusun Kampungsawah, Mulyasari. The village, Ciampel District, has not been optimally implemented because, (i) religious lessons are generally taught only 2 hours per week, on average, (ii) background understanding and appreciation of diverse Islamic life, (iii) understanding that children's education lessons do not contribute directly to the skills required in the world of work. These problems impact the knowledge, attitudes, and skills of children's education outcomes which are still not optimal. This study uses quantitative methods with data collection techniques by distributing questionnaires, and data analysis is carried out after completing data collection and using statistics to test hypotheses. Reciting Al-Qur'an; (2) data on students' interest in PAUD learning is carried out by distributing questionnaires; (3) PAUD results in data are taken from the final school exam scores for the 2021 academic year. Students with good reading skills in Children's Education tend to have high learning outcomes. Student learning interest is significantly related to student achievement in Children's Education lessons. There is a positive relationship between the variables in this study simultaneously, namely the Qur'an. They are reading ability and interest in learning, with student achievement in Children's Education subjects.